AT LAST A SOUTH AFRICAN PROPER LAW OF DELICT Burchell v Anglin 2010 3 SA 48 (ECG) - Frans E Marx (Obiter, 2021)
The laws of defamation all over the world share a common denominator – the balancing of two basic human rights: the right to freedom of expression and the right to reputation. In spite of this common objective, the laws pertaining to defamation often differ substantially from country to country and courts are often reluctant to apply legal rules or recognize judgments of foreign courts in this regard. Until recently the question as to which law to apply in cases involving delict was neglected in most legal systems. Although this position has changed in many countries as a result of technological development as well as modern communication systems, South African choice of law in delict remained almost non-existent. In spite of the prevalence of the lex fori as connecting factor under the influence of Von Savigny in the past, and until recently in England, it is today generally accepted that the lex loci delicti should, at least as a point of departure, be used as the connecting factor in delict. As Forsyth points out, the application of the lex loci delicti is in accord with the locus regit actum principle as well as the vested rights theory. The application of the lex loci delicti is not without problems however. One problem is that the place where the delict was committed is not always clear. The elements constituting the delict may have their origin in different jurisdictions. A product manufactured in one country, may cause damage in another. Is the lex loci delicti the place where the conduct (manufacturing) took place or the place where the damage was caused? Moreover, harm may be caused in different countries where the defective products are available. Another example is defamation. A defamatory statementpublished in one country may cause damage in another jurisdiction. The problem becomes even more prevalent where a defamatory statement is uploaded on the Internet. A statement uploaded on a server in one country can be and generally is accessible in a multiplicity of countries. To complicate matters further, the statement may cause pecuniary damage in one or more countries and personality infringement in another. Moreover, because the requirements for defamation are closely linked to public policy and a country’s attitude towards the protection of freedom of expression, the statement may be regarded as defamatory in one country but not in another. A second problem is that the lex loci delicti may be perfectly clear, but may be almost irrelevant. The typical example is illustrated in the American case of Babcock v Jackson (191 NE 2d 279 (1963)), where a car, registered and insured in New York with driver and passengers resident in New York, left the road in Ontario during an over-the-border drive with resultant injury to one of the passengers. In this scenario the place where the delict occurred is clearly Ontario but this single fact is less significant than all the other factors that have connection with the delict and the parties, namely New York. The lex loci delicti rule fails to assign an appropriate system in this type of case. That is the reason why the New York court in Babcock applied New York law. In South Africa very little case law exists regarding the choice of law in delict and, until now, regarding choice-of-law in defamation. The few casesthat were reported did not deal with the matter satisfactorily. The matter is therefore still very much res nova and open to our courts to break new ground. This is exactly why the judgment of Crouse AJ in Burchell v Anglin (2010 3 SA 48 (ECG)) can be regarded asa ground-breaking decision.